KAJIAN KEBUDAYAAN KAMPUNG ARAB DI MANADO - Prijadi, Ryo Kurniawan (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Archipelagic architectural culture found in City Villages in Manado City, which has a real form based on activities, values ​​and norms, and artifacts in the form of objects, so that the origin and meaning of the forms of ornament and infrastructure needed for village development planning can be known. city, so that it is useful for the existing community. orientation of human life in line with religious teachings. Several things can be concluded from the spatial planning, there are several factors, differences in perspective and in each form of this Cultural Form, due to cultural and environmental backgrounds, there are differences in the area.